Description of a new species and a new group of Salassa Moore, 1859 (Lepidoptera: Saturniidae) with a molecular study based on partial COI - Zheng, Xuhongyi; Wang, Dong (Zootaxa, 2023)
Salassa is a genus of the family Saturniidae. It comprises over 30 species that are widely distributed in Asia. This study describes a new species, Salassa sunwukongi sp. nov., found in Chinese Yunnan province. The first molecular study of Salassa was conducted using COI fragments. Molecular and morphological analyses revealed the presence of a monophyletic group, royi-group, distributed in the Himalayas. A key to members of the royi-group, along with species lists and distinguishing characteristics of all three groups of Salassa, is provided.